You are on page 1of 2

𝑦´´´´ − 2𝑦´´´ + 𝑦´´ = 𝑒 𝑥 + 1

Solución E.D Homogénea

𝑦 = 𝑒 𝑚𝑥
𝑦´ = 𝑚𝑒 𝑚𝑥

𝑦´´ = 𝑚2 𝑒 𝑚𝑥
𝑦´´´ = 𝑚3 𝑒 𝑚𝑥

𝑦´´´´ = 𝑚4 𝑒 𝑚𝑥

𝑚4 𝑒 𝑚𝑥 − 2𝑚3 𝑒 𝑚𝑥 + 𝑚2 𝑒 𝑚𝑥 = 0

𝑒 𝑚𝑥 (𝑚4 − 2𝑚3 + 𝑚2 ) = 0

𝑒 𝑚𝑥 ≠ 0

𝑚2 (𝑚2 − 2𝑚 + 1) = 0

𝑚2 (𝑚 − 1) (𝑚 − 1)
𝑚1 = 0 𝑚2 = 0 𝑚3 = 1 𝑚4 = 1

𝑦𝑐 = 𝑐1 + 𝑐2𝑥 + 𝑐3𝑒 𝑥 + 𝑐4𝑥𝑒 𝑥


Solución Particular

𝑔(𝑥) = 𝑒 𝑥 + 1

𝐿1 = 𝐷 − 1
𝐿2 = 𝐷
𝐿1 ∗ 𝐿2 = 𝐷(𝐷 − 1)

𝐷 (𝐷 − 1) (𝐷 4 − 2𝐷 3 + 𝐷 2 ) = 𝐷(𝐷 − 1)(𝑒 𝑥 + 1)

𝐷 3 (𝐷 − 1)3 = 0

𝑦 = 𝑐1 + 𝑐2𝑥 + 𝑐3𝑒 𝑥 + 𝑐4𝑥𝑒 𝑥 + 𝑐5 𝑥 2 + 𝑐6𝑥 2 𝑒 𝑥


𝑦𝑝 = 𝐴𝑥 2 + 𝐵𝑥 2 𝑒 𝑥

𝑦´𝑝 = 2𝐴𝑥 + 2 𝐵𝑥𝑒 𝑥 + 𝐵𝑥 2 𝑒 𝑥

𝑦´´𝑝 = 2𝐴 + 2 𝐵𝑒 𝑥 + 2 𝐵𝑥𝑒 𝑥 + 2𝐵𝑥𝑒 𝑥 + 𝐵𝑥 2 𝑒 𝑥 = 2𝐴 + 2 𝐵𝑒 𝑥 + 4 𝐵𝑥𝑒 𝑥 + 𝐵𝑥 2 𝑒 𝑥

𝑦´´´𝑝 = 2 𝐵𝑒 𝑥 + 2 𝐵𝑒 𝑥 + 2 𝐵𝑥𝑒 𝑥 + 2𝐵𝑒 𝑥 + 2𝐵𝑥𝑒 𝑥 + 2𝐵𝑥𝑒 𝑥 + 𝐵𝑥 2 𝑒 𝑥 =6 𝐵𝑒 𝑥 +6 𝐵𝑥𝑒 𝑥


+𝐵𝑥 2 𝑒 𝑥
𝑦´´´´𝑝 = 12 𝐵𝑒 𝑥 +8 𝐵𝑥𝑒 𝑥 + 𝐵𝑥 2 𝑒 𝑥
𝑦´´´´ − 2𝑦´´´ + 𝑦´´ = 𝑒 𝑥 + 1

12 𝐵𝑒 𝑥 +8 𝐵𝑥𝑒 𝑥 +𝐵𝑥 2 𝑒 𝑥 − 2(6 𝐵𝑒 𝑥 +6 𝐵𝑥𝑒 𝑥 +𝐵𝑥 2 𝑒 𝑥 ) + 2𝐴 + 2 𝐵𝑒 𝑥 + 4 𝐵𝑥𝑒 𝑥 +


𝐵𝑥 2 𝑒 𝑥 = 𝑒 𝑥 + 1
12 𝐵𝑒 𝑥 +8 𝐵𝑥𝑒 𝑥 +𝐵𝑥 2 𝑒 𝑥 − 12 𝐵𝑒 𝑥 +12 𝐵𝑥𝑒 𝑥 +2 𝐵𝑥 2 𝑒 𝑥 + 2𝐴 + 2 𝐵𝑒 𝑥 + 4 𝐵𝑥𝑒 𝑥 +
𝐵𝑥 2 𝑒 𝑥 = 𝑒 𝑥 + 1
2𝐴 + 2 𝐵𝑒 𝑥 = 𝑒 𝑥 + 1
2𝐵 =1
1
𝐵=
2

2𝐴=1
1
𝐴=2

Solución total

𝑦𝑇 = 𝑦𝑐 + 𝑦𝑝

1 2 1 2 𝑥
𝑦 = 𝑐1 + 𝑐2𝑥 + 𝑐3𝑒 𝑥 + 𝑐4𝑥𝑒 𝑥 + 𝑥 + 𝑥 𝑒
2 2